Linkages between financial and macroeconomic indicators in emerging markets and developing economies - Biswas, Rita; Liang, Zhongwen; Loungani, Prakash; Michaelides, Michael (My University, 2024)
This paper provides empirical evidence on the finance-growth nexus, making key contributions by focusing on previously understudied Emerging Markets and Developing Economies (EMDEs) and employing mixed-frequency data. Utilizing panel forecasting models for 50 countries from 1990 to 2019, we examine the empirical link between macroeconomic indicators (e.g., aggregate production) and financial indicators (e.g., stock market indexes). Our results support the notion that financial indicators can indeed serve as robust predictors of macroeconomic indicators. Further, the use of mixed data sampling (MIDAS) models enhances the results, confirming the presence of valuable predictive information in higher-frequency data, even for lower-income countries. These findings bear particular significance for policymakers and investors, given the persistent challenge of accessing timely and reliable data on real indicators in EMDEs.
Keywords: Finance-growth nexus; Macrofinance; MIDAS; EMDEs; Financial indicators; Predicting macroeconomic indicators